2021
DOI: 10.3390/ijerph181910151
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Assessment and Health Risk of Heavy Metals in Soils and Tea Leaves in the Southwest Region of China

Abstract: The collaborative assessment and health risk evaluation of heavy metals (HMs) enrichment in soils and tea leaves are crucial to guarantee consumer safety. However, in high soil HM geochemical background areas superimposed by human activities, the health risk associated with HMs in soil–tea systems is not clear. This study assessed the HMs concentration (i.e., chromium (Cr), cadmium (Cd), arsenic (As), and lead (Pb)) in tea leaves and their relationship with soil amounts in the southwest region of China to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…6 Liu et al analyzed heavy metals in tea leaves in the southwest region of Yunnan province, China, and found that the THQs for Cd and As were 0.007 and 0.136, respectively, and the HI value was 0.452. 6 Zhang et al found that Cd and As concentrations were higher in mature tea leaves, ranging from 0.012 to 0.092 and 0.073 to 0.456, than in young tea leaves, where concentrations ranged from 0.040 to 0.087 and 0.189 to 0.453; they also found that the HI in mature tea leaves was above 1 by 38.46% in Guizhou province, China, indicating a potential health risk for adults via the consumption of mature tea infusions. 13 Li et al found that Cd concentrations (0.2 mg/ L) in tea infusions were below the maximum limits, and that the THQ ranged from 2.33 × 10 −5 to 1.47 × 10 −1 and HI from 1.41 × 10 −2 to 3.45 × 10 −1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Liu et al analyzed heavy metals in tea leaves in the southwest region of Yunnan province, China, and found that the THQs for Cd and As were 0.007 and 0.136, respectively, and the HI value was 0.452. 6 Zhang et al found that Cd and As concentrations were higher in mature tea leaves, ranging from 0.012 to 0.092 and 0.073 to 0.456, than in young tea leaves, where concentrations ranged from 0.040 to 0.087 and 0.189 to 0.453; they also found that the HI in mature tea leaves was above 1 by 38.46% in Guizhou province, China, indicating a potential health risk for adults via the consumption of mature tea infusions. 13 Li et al found that Cd concentrations (0.2 mg/ L) in tea infusions were below the maximum limits, and that the THQ ranged from 2.33 × 10 −5 to 1.47 × 10 −1 and HI from 1.41 × 10 −2 to 3.45 × 10 −1 .…”
Section: Discussionmentioning
confidence: 99%
“…A THQ value less than 1 indicates an acceptable risk of harmful material exposure from tea, whereas HI < 1, HI > 1, and HI > 1 indicate no obvious negative impact, a high possibility of negative effects, and chronic toxicity, respectively . Liu et al analyzed heavy metals in tea leaves in the southwest region of Yunnan province, China, and found that the THQs for Cd and As were 0.007 and 0.136, respectively, and the HI value was 0.452 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of the results was determined by subjecting the data to a Q-test, which removed asymmetrical errors from the observations (n = 3) at a 95% confidence level. The quality of the results was assured by comparing them to standard reference materials for soil (GBW07605) [45] and plants (GBW08513) [46] from the National Research Center for Standards of China. The Cd retrieval percentage from the soil was 94.7%.…”
Section: Quality Assurance and Controlmentioning
confidence: 99%